Effect of bonding parameters on compression mechanical properties of bi-directional corrugated honeycomb aluminum. Issue 4 (12th March 2022) - Xing, Youdong; Yang, Siyi; Lu, Shiqing; Zhang, Pengfei; An, Yukun; Zhai, John
ABSTRACT: Bi-directional corrugated honeycomb aluminum has two-way energy absorption performance intended to be used as impact limiter filling material for nuclear spent fuel transport casks. It is made of aluminum plate, corrugated plate and adhesive. The bonding parameters determine the bonding effect of Bi-directional corrugated honeycomb aluminum thus affect the energy absorption performance. This paper verifies the bonding parameters from three aspects (type of adhesive, surface roughness, and thickness of the adhesive layer). The results show that when an acrylic adhesive is used to perform the compression test, no matter which bonding parameters are used, all samples debond. When an epoxy resin is used, except for the sample with an adhesive layer thickness of 0.2 mm and the surface was polished with the grit number of 320 sandpaper, samples with other parameters showed debonding to varying degrees. In addition, the bonding parameters have a great influence on the energy absorption performance of the specimen. The deformation and the energy absorption was also discussed.